Allelopathic effects of green manure cover crops on the germination and growth of blackjack (Bidens pilosa L.) and rapoko grass [Eleusine indica (L.) Gaertn] - Rugare, Joyful Tatenda (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhDAgric)--Stellenbosch University, 2018.